Repeated Low Intensity Blast Exposure Is Associated with Damaged Endothelial Glycocalyx and Downstream Behavioral Deficits - Hall, Aaron A.; Mendoza, Mirian I.; Zhou, Hanbing; Shaughness, Michael; McCarron, Richard M.; Ahlers, Stephen T. (Frontiers in Behavioral Neuroscience, 2017)
Current clinical research into mild traumatic brain injury (mTBI) has focused on white matter changes as identified by advanced MRI based imaging techniques. However, perivascular tau accumulation in the brains of individuals diagnosed with mTBI suggests that the vasculature plays a key role in the pathology. This study used a rat model to examine whether the endothelial glycocalyx, a layer of the vasculature responsible for sensing luminal shear forces, is damaged by exposure to repeated low intensity blast, and whether this layer is associated with observed behavioral deficits. The blast exposure used consisted of 12, 40kPa blast exposures conducted with a minimum of 24 hours between blasts. We found that repeated blast exposure reduced glycocalyx length and density in various brain regions indicating damage. This blast exposure paradigm was associated with a mild performance decrement in the Morris water maze (MWM) which assesses learning and memory. Administration of hyaluronidase, an enzyme that binds to and degrades hyaluronan (a major structural component of the glycocalyx) prior to blast exposure reduced the observed behavioral deficits and induced a thickening of the glycocalyx layer. Taken together these findings demonstrate that the endothelial glycocalyx degradation following repeated blast is associated with behavioral decrements which can be prevented by treatment with hyaluronidase.